Effect of Retro‐Inverso Isomer of Bradykinin on Size‐Dependent Penetration of Blood–Brain Tumor Barrier. Issue 7 (2nd January 2018) - Su, Bingxia; Wang, Ruifeng; Xie, Zuoxu; Ruan, Huitong; Li, Jichen; Xie, Cao; Lu, Weiyue; Wang, Jing; Wang, Dongli; Liu, Min
Abstract: Retro‐inverso bradykinin (RI‐BK) has better metabolic stability and higher affinity for the BK type 2 (B2) receptor, compared with bradykinin. At low doses, RI‐BK can selectively enhance the permeability of the blood–brain tumor barrier (BBTB) without harming normal brain tissue. In this study, gold nanoparticles (GNPs) of size ranging from 5 to 90 nm are synthesized to assess the optimal size of nanocarriers that achieves maximum brain accumulation after the treatment of RI‐BK. The ability of the GNPs to cross the BBTB is tested in a rat C6 glioma tumor model. The results of inductively coupled plasma–mass spectrometry and transmission electron microscopy indicate that GNPs with size of 70 nm achieve maximum permeability to the glioma. The present study supports the conclusion that RI‐BK can enhance the permeability of BBTB and provides fundamental information for further development of nanomedicines or nanoprobes for glioma therapy. Abstract : Gold nanoparticles (GNPs) ranging from ≈5‐90 nm are engineered to mimic nanocarriers of various sizes. The ability of the GNPs to cross the blood‐brain tumor barrier (BBTB) is investigated in tumor bearing rats. The results indicate that 70 nm GNPs enabled maximum drug delivery to the glioma after the BBTB breakdown induced by retro‐inverso bradykinin (RI‐BK).